Beyond the existing economic uncertainty: Spa enterprises' resilience capacity in the Polish tourism sector - Diana Dryglas; Marcin Salamaga (Entrepreneurial Business and Economics Review (EBER), 2023)
Objective: The study aimed to identify and assess factors that build the resilience capacity of spa enterprises within the tourism sector in Poland in the wake of the economic crisis from managers' perspective. Research Design & Methods: Research method characteristic for quantitative research was used. Survey data were collected from 500 tourism enterprise managers (including 80 from the spa sector) in Poland, using a self-administered questionnaire. A two-proportion Z-test was used to verify whether there were any significant differences in the percentage of selected response variants between the tourism sector and spa enterprises. Findings: The methods used made it possible to assess financial, social, and human capital in spa enterprises as compared to the tourism sector. The results revealed that (1) the coronavirus pandemic had a more devastating impact on the financial standing of spa enterprises than on the financial situation in the tourism sector, (2) spa enterprises are more willing to use resilience actions on the regional and governmental levels than the tourism sector, and (3) spa enterprises and the tourism sector have a demand for digital competencies under their short-term and long-term recovery strategies. Implications & Recommendations: The findings help to provide recommendations for spa and tourism enterprises for adapting their financial, social, and human policy to foster their resilience capacity and help them recover. Contribution & Value Added: Regarding the empirical part, the results of this study contribute to the scholarly understanding of the resilience capacity of spa and tourism enterprises and the way spa and tourism enterprises assess resilience factors in response to the economic crisis. The present study will help managers of spa and tourism enterprises recognise resilience as a crisis management tool or strategy for business stability and adaptability to economically uncertain environment and new circumstances.
Keywords: M20; M21; 330; economic crisis; Poland; quantitative research; resilience; spa enterprise; tourism sector